2018
DOI: 10.1101/447367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling the polygenic architecture of complex traits using blood eQTL metaanalysis

Abstract: SummaryWhile many disease-associated variants have been identified through genome-wide association studies, their downstream molecular consequences remain unclear.To identify these effects, we performed cis- and trans-expression quantitative trait locus (eQTL) analysis in blood from 31,684 individuals through the eQTLGen Consortium.We observed that cis-eQTLs can be detected for 88% of the studied genes, but that they have a different genetic architecture compared to disease-associated variants, limiting our ab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
733
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(768 citation statements)
references
References 99 publications
16
733
2
Order By: Relevance
“…(23,31) In addition, GWAS have identified associations between this allele and increased risk of childhood acute lymphoblastic leukemia in males, non-melanoma skin cancer, squamous cell carcinoma, cutaneous squamous cell carcinoma, basal cell carcinoma, actinic keratosis, and progressive supranuclear palsy(Figure 2b). (23) Both rs12203592 and rs62389423 risk alleles identified in our AML/MDS patients associated in eQTLGen consortium analyses with increased expression of IRF4, P=1.48x10-29 and P=1.4x10-22, respectively(21).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…(23,31) In addition, GWAS have identified associations between this allele and increased risk of childhood acute lymphoblastic leukemia in males, non-melanoma skin cancer, squamous cell carcinoma, cutaneous squamous cell carcinoma, basal cell carcinoma, actinic keratosis, and progressive supranuclear palsy(Figure 2b). (23) Both rs12203592 and rs62389423 risk alleles identified in our AML/MDS patients associated in eQTLGen consortium analyses with increased expression of IRF4, P=1.48x10-29 and P=1.4x10-22, respectively(21).…”
mentioning
confidence: 90%
“…To better understand the potential function of the variants identified by GWAS and ASSET analyses we annotated significant SNPs using publicly available data. eQTLGen, a consortium analyses of the relationship of SNPs to gene expression in 30,912 whole blood samples, was used to determine if significant and suggestive SNPs (p<5 x 10-6) were whole blood cis-eQTL, defined as allele specific association with gene expression (21). Genotype-Tissue Expression project (GTEx) was used to test for significant eQTLs in >70 additional tissues (22).…”
Section: Functional Annotation Of Genetic Variation Associated With Amentioning
confidence: 99%
“…These studies have showed that the majority of eQTLs are located in cis, that is less than 1 Mb away of the gene they control, and that population‐specific eQTLs are driven by changes in allelic frequency rather than gene × gene or gene × environment interactions . While a few trans ‐ associations—involving genes located on different chromosomes—were detected, these associations were either weak or driven by cross mapping errors and changes in cellular composition . The strong potential of eQTL for biomedical applications has rapidly lead to extend this framework to multiple tissues or purified immune cell types, showing a strong tissue specificity of eQTLs.…”
Section: Genetic Control Of Transcriptional Activity Is Highly Stimulmentioning
confidence: 99%
“…59 While a few trans-associations-involving genes located on different chromosomes-were detected, these associations were either weak or driven by cross mapping errors 60 and changes in cellular composition. 61 The strong potential of eQTL for biomedical applications 62 has rapidly lead to extend this framework to multiple tissues 63 or purified immune cell types, 29,64 showing a strong tissue specificity of eQTLs. Furthermore, exposing human cells to immune and infectious challenges has allowed the identification of response eQTLs that are associated with changes in gene expression specifically upon immune stimulation ( Figure 1F,G).…”
Section: Genetic Control Of Transcriptional Activity Is Highly Stimmentioning
confidence: 99%
“…To aid prioritisation of HiChIP target genes, we interrogated expression quantitative trait locus (eQTL) data from the largest study of whole blood gene expression [17] and TCGA endometrial tumors [18]. Using these data, we evaluated the overlap between endometrial cancer risk CVs and the top eQTL variants for each HiChIP target gene.…”
Section: Hichip Target Gene Expression Associates With Cvsmentioning
confidence: 99%